The national assembly and the post-legislative scrutiny issue under the constitution of Vietnam - Nguyen, Thi Hong Yen (Đại học Quốc Gia Hà Nội, 2020)
In Vietnam, legislative oversight is a means to hold the government and other state actors accountable for their actions and ensure their actions in accordance with the law. Effective oversight is applied to ensure transparency and openness, to create the interactive environment where actions of government and other actors are debated and receive public input, to scrutinize government policies to ensure they have been implemented adequately and have obtained the desired impact; etc. How does the National Assembly implement Post-Legislative Scrutiny and gain valuable experiences? And how can the National Assembly improve its capacity to this issue? To answer these questions, this article will focus on clarifying issues related to the PostLegislative Scrutiny of the National Assembly under then Constitution and laws of Vietnam, the difficulties and challenges that the National Assembly is facing, thereby recommending solutions to strengthen the capacity as well as the effectiveness of post-legislative monitoring activities of the Vietnamese Parliament in the next stage.